Analysis Of The Influence Of Financial Literacy, Ease Of Use, Risk Perception, And Decision To Use QRIS As Digital Payment On FE Students Of Sarjanawiyata Tamansiswa University Yogyakarta - Desniawaty Desniawaty; Pristin Prima Sari; Johannes Maysan Damanik (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The purpose of this study is to assess the influence of financial literacy, ease of use, and risk perception on the decision to use QRIS in students of the Faculty of Economics, Sarjanawiyata Tamansiswa University. This study uses a kunitative research method, and sampling is carried out with a purposive sampling approach. This study involved 100 active FE UST students. Data collection was carried out through a questionnaire distributed through a google form with a likert scale of 1-5. Data validity and reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis tests were carried out using the SPSS Ver 25 statistical tool. The results of the study show that partially, the financial literacy of FE UST students has a positive and significant effect on their decision to use QRIS; the ease of use of QRIS has a positive and significant effect on their decision to use QRIS; and the perception of risk negatively affects their decisions. Simultaneously, this shows that financial literacy, ease of use, and risk perception positively and significantly influence QRIS decisions.